2021
DOI: 10.1128/aac.01193-20
|View full text |Cite
|
Sign up to set email alerts
|

BKC-2, a New BKC Variant Detected in MCR-9.1-Producing Enterobacter hormaechei subsp. xiangfangensis

Abstract: We performed the characterization of a multidrug-resistant (MDR) Enterobacter spp. isolate highlighting the genetic aspects of the antimicrobial resistance genes. An Enterobacter spp. isolate (Ec61) was recovered in 2014 from a transtracheal aspirate sample from a patient admitted to a Brazilian tertiary hospital and submitted to further microbiological and genomic characterization. Ec61 was identified as Enterobacter hormaechei subsp. xiangfangensis ST451, showed a MDR profile and the presence of genes codify… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 17 publications
0
1
0
Order By: Relevance
“…One of the factors is a two-component regulatory system encoded by qseC/qseB downstream of mcr-9, as reported in an E. coli isolate harboring mcr-9 (21). Four other studies (25,(32)(33)(34), however, reported that mcr-9-positive isolates carrying qseC/qseB were susceptible to colistin, including 10 isolates of Salmonella and E. coli (32), and one isolate each of E. xiangfangensis (25), Citrobacter telavivum (33), and Enterobacter hormaechei (34). In contrast, four additional studies (35)(36)(37)(38) reported that mcr-9-positive isolates without qseC/qseB were resistant to colistin, including one isolate each of Salmonella Newport (35), Enterobacter kobei (36,37), Enterobacter roggenkampii (38).…”
Section: Resultsmentioning
confidence: 82%
“…One of the factors is a two-component regulatory system encoded by qseC/qseB downstream of mcr-9, as reported in an E. coli isolate harboring mcr-9 (21). Four other studies (25,(32)(33)(34), however, reported that mcr-9-positive isolates carrying qseC/qseB were susceptible to colistin, including 10 isolates of Salmonella and E. coli (32), and one isolate each of E. xiangfangensis (25), Citrobacter telavivum (33), and Enterobacter hormaechei (34). In contrast, four additional studies (35)(36)(37)(38) reported that mcr-9-positive isolates without qseC/qseB were resistant to colistin, including one isolate each of Salmonella Newport (35), Enterobacter kobei (36,37), Enterobacter roggenkampii (38).…”
Section: Resultsmentioning
confidence: 82%
“…Multiple Enterobacterial species, including Salmonella ( 45 ), E. coli ( 45 ), E. asburiae ( 50 ), Citrobacter telavivum ( 51 ), and E. hormaechei ( 52 ) with the so-called qseBC genes, have been reported to exhibit colistin-susceptible phenotypes. In contrast, some other studies also found that lack of such a tandem system in certain bacterial species was associated with colistin-resistant phenotypes, as with E. roggenkampii ( 34 ), E. cloacae complex ( 48 ), and S .…”
Section: Discussionmentioning
confidence: 99%
“…que confere resistência às polimixinas. [154][155] O gene mcr-9 estava abrigado em um plasmídeo IncHI2/IncHI2A em seu ambiente genético é composto pelo gene rcnR, que codifica um repressor do gene rcnA, que é uma bomba de efluxo de níquel e cobalto além de pcoE e pcoS que são envolvidos em resistência ao cobre. A presença destes genes sugere que esta linhagem também seja resistente a estes metais.…”
Section: O Impacto Da Presença Do Plasmídeo Carreando Blakpc Em E Col...unclassified